Deep tissue massage, strengthening and stretching exercises, and a combination of both compared with advice to stay active for subacute or persistent non-specific neck pain: A cost-effectiveness analysis of the Stockholm Neck trial (STONE). (April 2020) - Pico-Espinosa, Oscar Javier; Aboagye, Emmanuel; Côté, Pierre; Peterson, Anna; Holm, Lena W.; Jensen, Irene; Skillgate, Eva
Abstract: Objective: To evaluate the cost-effectiveness of deep tissue massage ('massage'), strengthening and stretching exercises ('exercises') or a combination of both ('combined therapy') in comparison with advice to stay active ('advice') for subacute and persistent neck pain, from a societal perspective. Methods: We conducted a cost-effectiveness analysis alongside a four-arm randomized controlled trial of 619 participants followed-up for one year. Health-related quality of life was measured using EQ-5D-3L and costs were calculated from baseline to one year. The interventions were ranked according to quality adjusted life years (QALYs) in a cost-consequence analysis. Thereafter, an incremental cost per QALY was calculated. Results: In the cost-consequence analysis, in comparison with advice, exercises resulted in higher QALY gains, and massage and the combined therapy were more costly and less beneficial. Exercises may be a cost-effective treatment compared with advice to stay active if society is willing to pay 17 640 EUR per QALY. However, differences in QALY gains were minimal; on average, participants in the massage group, spent a year in a state of health valued at 0.88, exercises: 0.89, combined therapy: 0.88 and, advice: 0.88. Conclusions: Exercises are cost-effective compared to advice given that the societal willingness to pay is above 17 640 EUR per year in full health gained. Massage and a combined therapy are not cost-effective. While exercise appeared to have the best cost/benefit profile, even this treatment had only a modest benefit and treatment innovation is needed. Advice to stay active remains as a good therapeutic alternative from an economical perspective. Highlights: Exercises are cost-effective compared to advice for persistent neck pain. Massage is not cost-effective compared to advice for persistent neck pain. A combined therapy is not cost-effective compared to advice for persistent neck pain. Differences between massage and/or exercises and advice in QALY gains are minimal. Advice is a good alternative for persistent neck pain from an economic perspective.